Cassava extension organization and activities in Thailand - Klakhaeng, Kaival I.; Boonmark, Charungsri; Chainuvat, Chavalvut (International Center for Tropical Agriculture, 1995)
Being easy to grow and drought tolerant, cassava is a popular crop among Thai farmers, particularly in the Northeast and East. The area planted annually is 1.28-1.60 million hectares. Because of drought and infertile soils in these areas, cassava yields average only 13-14 t/ha with about 18 percent starch. The price of fresh roots is about US$28-30/tonne. In the past only the local varieties were grown all over the country. In 1984, a better variety, Rayong 3, was introduced to the farmers. It is characterized not only by high yield but also by high starch content. Later, other new varieties have been released by the research institutes and universities. The government has therefore allocated a budget to multiply and promote new cassava varieties. This long-term program started in 1993 and will continue until 1998. Due to changes in the Common Agricultural Policy of the European Economic Community, the government policy makers expect that the cassava price in the EEC will decline. The government is therefore making an effort to reduce the cassava area by promoting the production of other perennial crops. Also, a large government budget has been provided to survey the potential area for cassava crop substitution. The future target of our program is for average cassava yields to increase to about 14.5 t/ha, while the recommended varieties will be cultivated in about 20 percent of the total cassava area by 1998